Educational diagnosis and opportunities for improvement framed in the quality management, ISO 9001: 2015 - Carhuaricra Meza, Julio C. (2024)
The study, “Educational diagnosis and opportunities for improvement framed in quality management, ISO 9001: 2015”, answered the following question: What are the weaknesses, strengths and aspirations of the training elements and processes framed in the ISO clauses? 9001:2015? Therefore, the objective was to begin the implementation of self-regulation activities aligned with constant improvement. Now, regarding the methods, techniques and instruments, the mixed, qualitative and quantitative case method was applied. Design, systemic. Likewise, the perspective of managing risks has been taken into account, which consisted of documentary analysis using the checklist, SWOT matrix and CAME. The main observation unit being the institutional educational project. Subsequently, the proposals were consolidated with virtual participatory workshops with focus groups, made up of experts, managers, teachers, students and parents. Therefore, the conclusions show the average progress in percentages of compliance with the clauses of the aforementioned international standard, organizational context = 74%; leadership = 69.5%; planning = 75%; support = 85.5%; operation = 88%; performance evaluation = 63% and improvement = 50%. Likewise, with respect to opportunities for improvement, priority was given to the implementation of a system for measuring learning achievements based on the entry and exit profiles according to the needs of educational development.